Empirically Based Play Interventions for Children. 2005
DOI: 10.1037/11086-009
|View full text |Cite
|
Sign up to set email alerts
|

Child ADHD Multimodal Program: An Empirically Supported Intervention for Young Children With ADHD.

Abstract: The Child ADHD (Attention Deficit Hyperactivity Disorder) Multimodal Program (CAMP) is an empirically supported intervention program for young children diagnosed with ADHD (8.5 years and younger). CAMP is designed to treat children, parents, and teachers and is conducted in 90minute, weekly training sessions. Children and their parents are separately and concurrently trained in a group context for 10 consecutive weeks. The children's training group includes behavioral management techniques, Preparation for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The games utilized in the GB-CBT model are rule-governed, typically team-based, and rely on friendly competition as an incentive for participation. Structured play provides the children with multiple opportunities to rehearse the various skills that are taught throughout the course of the group, thereby facilitating greater learning and retention Reddy, Spencer, Hall, & Rubel, 2001;Reddy, Springer, et al, 2005). Structured play also serves to enhance group cohesion through active participation and enables the process of therapy to become more fluid, reducing defensiveness (Gil, 1991;Kelly & Odenwalt, 2006).…”
Section: Gb-cbt Componentsmentioning
confidence: 95%
“…The games utilized in the GB-CBT model are rule-governed, typically team-based, and rely on friendly competition as an incentive for participation. Structured play provides the children with multiple opportunities to rehearse the various skills that are taught throughout the course of the group, thereby facilitating greater learning and retention Reddy, Spencer, Hall, & Rubel, 2001;Reddy, Springer, et al, 2005). Structured play also serves to enhance group cohesion through active participation and enables the process of therapy to become more fluid, reducing defensiveness (Gil, 1991;Kelly & Odenwalt, 2006).…”
Section: Gb-cbt Componentsmentioning
confidence: 95%
“…The importance of providing a framework to children with clearly delineated rules and behavioral expectations within the context of group therapy has been discussed in the literature (Golden-Mandell et al, 1989;Johnson & Young, 2007;Martin & Pear, 2007;McMullin, 2000;Reeker et al, 1997;Reddy, Spencer, Hall, & Rubel, 2001;Reddy, Springer et al, 2005;Rice-Smith, 1993;Shechtman & Gluk, 2005). Research has shown that a structured group therapy setting with clear behavioral expectations creates a sense of safety for children, demonstrates adults' ability to handle various situations, and facilitates behavioral modification (Johnson & Young, 2007;Reeker et al, 1997;Reddy et al, 2001;Reddy, Springer et al, 2005;RiceSmith, 1993;Shechtman & Gluk, 2005).…”
Section: Group Structurementioning
confidence: 98%
“…DAGs have been successfully utilized for treating childhood ADHD and social skills deficits (Reddy, Files-Hall, & Schaefer, 2005;Reddy, Springer et al, 2005), and they have been shown to be effective for improving prosocial behaviors, self-efficacy, internalizing symptoms, oppositionality, aggression, hyperactivity, distractibility, and levels of parental stress (Reddy, Springer et al, 2005). Many of these symptoms are common among children who have experienced sexual abuse (Kendall-Tackett et al, 1993).…”
Section: Play Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…nents primarily through developmentally appropriate games (DAGs), a play therapy technique that has shown promise for treating a number of problems such as attention-deficit hyperactivity disorder (ADHD) and social skills deficits (BayHinitz, Peterson, & Quilitch, 1994;Reddy, Spencer, Hall, & Rubel, 2001;Reddy et al, 2005;Springer & Reddy, 2010;Swank, 2008).…”
mentioning
confidence: 98%